Mastering Performance-Based Tools for University Classrooms: How Forum Theatre Transforms Teachers - Malinina, Irina (Cultural Arts Research and Development, 2024)
Teaching as a social practice involves a holistic approach, including continuous interaction with all the social actors of the educational process as well as feelings, emotions, body movements, and voice. Few higher education institutions provide teacher preparation programs that integrate and prioritize corporeality alongside social-emotional learning (SEL) and its elements, such as empathy, emotional intelligence and social awareness. The gap between the theory and real-life teaching can be bridged through performance-based tools, such as forum theatre, in a teacher training course at universities or colleges. Such tools represent a transdisciplinary approach between drama and pedagogy with sketches or vignettes as the main technique eliciting discussion and personal reminiscences among students. The corporeality of performance sketches, inherent to any professional practice, and their spatial and temporal resemblance to real teaching settings are what imbibe this approach. The article demonstrates how this approach can be implemented in teacher education. It argues that applying these methods when teaching both pre-service and in-service teachers can transform the teachers’ understanding of the inner world of their students, contributing to a better teachers’ cognitive and emotional empathy towards students. By using the Forum Theatre, teachers can address learners’ needs and interests and advocate for them with other actors in the educational process by being empathetic and attentive to classroom accommodations, extracurricular activities, learners’ sense of belonging, and by raising awareness among stakeholders in the learning process.